"And your wedding is the twenty-second <.> of June is it?" - Barron, Anne (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
This chapter addresses the lack of systematic research into the use of tag questions in Irish English on a formal and functional level by conducting an exploratory genre-specific analysis of tag questions in service encounters in Irish English. Tag question usage is compared with previous findings from reference corpora of Irish English, British English and American English. The study points to many similarities between tag questions across genre and variety but also shows features which appear particular to present day Irish English, such as the use of sure-tags a higher frequency of the operator BE, a more frequent canonical use of “is it?” tag questions and a high use of interrogative anchors. In addition, the confirmation-eliciting function was employed particularly frequently in the canonical tag questions recorded in the service encounter data. Further research is required to investigate whether this findings was genre-related or varietyrelated. Finally, non-concordant tag uses were found to be uncommon, a finding which contrasts with previous research on Irish English. The paper closes with a plea for an increase in cross-variational analyses of tag questions.
Tag questions in Irish English
Keywords: 420 Englisch, Altenglisch